The Eaton-Gersovitz-Arellano environment with collateral - Guinsburg, Pedro Vaissman (2014)
In this article I introduce collateralization in the Eaton-Gersovitz-Arellano environment. In my paper, collateral can be understood as Foreign Direct Investment. I find that collateral increases the equilibrium levels of defaultable debt and, at the same time, avoids the use of default. Restrictions of collateral leads to higher use of default in equilibrium.